Human Health and Environmental Impact of Electronic Waste in Hadejia Metropolis, Jigawa State, Nigeria - Bashir B. Sabo; Aminu Hussaini (International Journal of Environmental Sciences, Development & Sustainability, 2026)
This study examined the impact of electronic waste (e-waste) disposal on human health and environmental quality in Hadejia. The rapid increase in the use of electrical and electronic equipment has resulted in a corresponding rise in e-waste generation, which poses significant environmental and public health challenges, especially in developing urban areas where waste management systems are inadequate. The study specifically assessed current e-waste disposal practices, evaluated the environmental and health effects of improper disposal, and identified factors influencing e-waste management within the study area. A descriptive survey research design was adopted, and data were collected from 150 respondents using structured questionnaires, interviews, and field observations. Data were analyzed using descriptive statistics such as frequencies and percentages, while inferential analysis was conducted using the Chi-square test to determine the relationship between e-waste disposal practices and socio-economic susta